2017
DOI: 10.1097/hp.0000000000000720
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Risk of Hematopoietic Acute Radiation Syndrome in Children

Abstract: Following a radiological terrorist attack or radiation accident, the general public may be exposed to radiation. Historically, modeling efforts have focused on radiation effects on a "reference man"-a 70-kg, 180-cm-tall, 20- to 30-y-old male-which does not adequately reflect radiation hazard to special populations, particularly children. This work examines the radiosensitivity of children with respect to reference man to develop a set of parameters for modeling hematopoetic acute radiation syndrome in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Further, radiation exposure is a matter of concern in children. Regarding acute radiation syndrome, it is reported that hematopoietic disorders are more likely to occur in children than in adults (14). Krille et al (15) investigated the late effects of exposure to ionizing radiation from CT in a pediatric case, suggesting that this was a risk factor for a secondary cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Further, radiation exposure is a matter of concern in children. Regarding acute radiation syndrome, it is reported that hematopoietic disorders are more likely to occur in children than in adults (14). Krille et al (15) investigated the late effects of exposure to ionizing radiation from CT in a pediatric case, suggesting that this was a risk factor for a secondary cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Computational modeling estimates that children can be twice as sensitive to acute effects of radiation, with younger children at greatest risk (54). Fortunately, Neupogen, Neulasta, Leukine, and Nplate have all been approved for adult and pediatric populations, and the Biomedical Advanced Research and Development Authority (BARDA), within the HHS, has procured all four MCMs for potential use in a mass casualty scenario.…”
Section: Pediatric Populationsmentioning
confidence: 99%
“…Recently, Leukinet (granulocyte-macrophage colony-stimulating factor; GM-CSF) was approved by the FDA as a radiomitigator to increase survival and to facilitate the recovery of white blood cells in adults and pediatric patients acutely exposed to a sub-lethal dose of radiation (12). Hematopoietic organs are highly susceptible to the cytotoxic effects of radiation, resulting in immune suppression including neutropenia, thrombocytopenia, and/or anemia (13)(14)(15). Patients with neutropenia often experience reduced defense against infection and inflammation, consequently followed by mortality due to sepsis (16).…”
Section: Introductionmentioning
confidence: 99%